Optimal Use of Proton Pump Inhibitors and Potassium-competitive Acid Blockers - Jong Kyu Park (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
A variety of proton pump inhibitors (PPIs) have been developed in Korea since the introduction of omeprazole (the first PPI) in 1989. PPIs have served as the basic therapeutic approach for the management of gastric acid-related diseases for 30 years and remain among the most widely used drugs. Recently, potassium-competitive acid blockers (PCABs) have been developed both in Korea and abroad, demonstrating superior or non-inferior effects compared to existing PPIs in treating gastroesophageal reflux disease or Helicobacter pylori eradication, among others. Indications vary based on the various types and dosages of PPIs and PCABs, and several factors, including patients’ underlying disease, safety profile, particularly with regard to drug-drug interactions, and types of formulations of PPIs and PCABs need to be considered prior to prescribing these medications. In this article, we discuss the criteria for reimbursement of various PPIs and PCABs in Korea, along with considerations for prescribing these drugs based on patients’ underlying diseases.